2012
DOI: 10.1371/journal.pone.0044497
|View full text |Cite
|
Sign up to set email alerts
|

Caffeine-Induced Activated Glucocorticoid Metabolism in the Hippocampus Causes Hypothalamic-Pituitary-Adrenal Axis Inhibition in Fetal Rats

Abstract: Epidemiological investigations have shown that fetuses with intrauterine growth retardation (IUGR) are susceptible to adult metabolic syndrome. Clinical investigations and experiments have demonstrated that caffeine is a definite inducer of IUGR, as children who ingest caffeine-containing food or drinks are highly susceptible to adult obesity and hypertension. Our goals for this study were to investigate the effect of prenatal caffeine ingestion on the functional development of the fetal hippocampus and the hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
84
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 103 publications
(93 citation statements)
references
References 59 publications
(57 reference statements)
5
84
0
1
Order By: Relevance
“…The hippocampus is the primary negative feedback regulatory center of the HPA axis (36). Additionally, caffeine can enter the fetus and directly inhibit 11β-HSD2 expression in the hippocampus.…”
Section: Discussionmentioning
confidence: 99%
“…The hippocampus is the primary negative feedback regulatory center of the HPA axis (36). Additionally, caffeine can enter the fetus and directly inhibit 11β-HSD2 expression in the hippocampus.…”
Section: Discussionmentioning
confidence: 99%
“…Another team has suggested that embryonic caffeine exposure produces an increase in body weight (B10%), alters cardiac function and morphology, and produces long-lasting alterations in DNA methylation (Buscariollo et al, 2014). A third group has focused on the neuroendocrine consequences and found that prenatal caffeine ingestion induces an increased susceptibility to metabolic syndrome with alterations of glucose and lipid metabolic phenotypes that then propagate transgenerationally (Katayama et al, 1987;Xu et al, 2012a;Xu et al, 2012b).…”
Section: Caffeinementioning
confidence: 99%
“…The concentrations of serum ACTH and CORT were measured by isotope labeling kit (Morgan, 2012) and ELISA kit (Xu et al, 2012b), respectively, following the manufacturer's protocols. The intra-assay and the inter-assay coefficients of variation for ACTH and CORT determination were 10% and 15%, 5.0% and 7.2%, respectively.…”
Section: Detection Methods and Indicatorsmentioning
confidence: 99%
“…Furthermore, the caffeine concentration in maternal blood was 254 ± 11 μM (49 ± 2 μg/ml) after intake of 120 mg/kg·d caffeine in our studies (Wang et al, 2013), which is only 1.6 times higher than the clinical signs of intoxication (~30 μg/ml), but did not reach the dose with fatalities (~80 μg/ml). In our previous studies (Xu et al, 2012b), we had used 20, 60 and 180 mg/kg·d of caffeine and observed some multi-index changes in 20 mg/kg·d and a clear dose-effect relationship. To achieve the typical IUGR model, the dose of 120 mg/kg·d caffeine was used, to verify the transgenerational effects in the present study.…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 98%